Diagnostic Value of Lachmeter in Measuring Anterior Tibia Translation on Post-Anterior Cruciate Ligament Tear Reconstruction Compared to CT Scan - Darmawan, Marsha Ruthy; Martadiani, Elysanti Dwi; Ayusta, Made Dwija Putra; Widiana, Gede Raka; Setiawan, Celleen Rei; Aryana, Gusti Ngurah Wien (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Anterior translation of the tibia (ATT) is a secondary sign of an anterior cruciate ligament (ACL) tear. With advances in technology, new tools such as the Lachmeter are expected to replace computed tomography scanning (CT scan) in measuring the ATT. AIM: This study aims to determine the diagnostic validity of the Lachmeter in measuring the ATT 6–12 months after ACL tear reconstruction. MATERIALS AND METHODS: A retrospective diagnostic test with a Lachmeter was used to measure ATT in patients 6–12 months after ACL tear reconstruction, compared with the gold standard CT scan and using a consecutive sampling technique. The optimal cutoff value of ATT was determined with Lachmeter afterwards. Statistical Package for the Social Sciences version 21.0 was used for the data analysis. RESULTS: There are 28 persons with a positive ATT (≥ 5 mm) and four people with a negative ATT (<5 mm) measured using CT scan out of 32 samples. The optimal cutoff of ATT with Lachmeter is ≥7.28 mm (Area under curve = 0.88, 95% CI, 0.67–1.00 and p = 0.004) with a sensitivity of 84.62%, specificity 83.33%, positive predictive value 95.65%, negative predictive value 55.56%, positive likelihood ratio (LR) 5.08, negative LR 0.18, and 84.38% accuracy. CONCLUSION: Lachmeter is a new tool for determining ATT that is highly efficient and easy to use. With good sensitivity and specificity values, this new tool has been proven to be very good at measuring ATT compared to CT scan as the gold standard.